THE EFFECT OF USING THREE-STEPS INTERVIEW TO IMPROVE STUDENT’S SPEAKING SKILL TOWARDS ELEVENTH GRADE STUDENTS OF SMA AL-AZHAR 3 BANDAR LAMPUNG IN ACADEMIC YEAR 2016/2017 - Erika Utami; Helta Anggia (LINGUISTIKA, 2016)
The focus of the object to be examined in this research is to find out if there is a improvement of using Three-Steps Interview in improving students’ speaking skill towards eleventh grades students of SMA Al-Azhar 3 Bandar Lampung in Academic Year 2016/2017. The research is an experimental research design which measure the score of pre-test and post-test as an appliance to know whether there is an effect of using Three-Steps Interview or not. The subject of this research is consisted of 58 students which are divided into experimental class and control class. The data is analyzed by using independent sample test. The result shows that students’ mean score of experimental and control class in post-test is significantly different. It shows the t-count is higher than t-table (11,871 > 2, 0032). Therefore, null hypotheses were rejected and alternative hypotheses were accepted. It means that there is an effect of using Three-Steps Interview to improve students’ speaking skill. These researches suggest that there is an effect of using Three-Steps Interview in improving students’ speaking skill towards eleventh grades students of SMA Al-Azhar 3 Bandar Lampung in Academic Year 2016/2017. In conclusion, Three-Steps Interview could be applied in teaching English process, especially in speaking.